Covalent Reactions on Chemical Vapor Deposition Grown Graphene Studied by Surface‐Enhanced Raman Spectroscopy. Issue 15 (1st March 2016) - Kovaříček, Petr; Bastl, Zdeněk; Valeš, Václav; Kalbac, Martin
Abstract: Graphene is a material of unmatched properties and eminent potential in disciplines ranging from physics, to chemistry, to biology. Its advancement to applications with a specific function requires rational design and fine tuning of its properties, and covalent introduction of various substituents answers this requirement. We challenged the obstacle of non‐trivial and harsh procedures for covalent functionalization of pristine graphene and developed a protocol for mild nucleophilic introduction of organic groups in the gas phase. The painstaking analysis problem of monolayered materials was addressed by using surface‐enhanced Raman spectroscopy, which allowed us to monitor and characterize in detail the surface composition. These deliverables provide a toolbox for reactivity of fluorinated graphene under mild reaction conditions, providing structural freedom of the species to‐be‐grafted to the single‐layer graphene. Abstract : Grafting graphene : Covalent functionalization of chemical vapor deposition (CVD) grown graphene was performed under mild conditions in the gas phase following a general protocol. Surface‐enhanced Raman spectroscopy (SERS) unequivocally confirms the functional groups grafted onto the monolayered material (see figure).